Molecular detection of SARS‐CoV‐2 and differentiation of Omicron and Delta variant strains. Issue 5 (13th March 2022) - Tsui, Wai Ning Tiffany; Hamill, Vaughn; Noll, Lance; Lu, Nanyan; Porter, Elizabeth Poulsen; Harbidge, Donald; Cox, Emily; Richardson, Claire; Gray, Mark; Sebhatu, Tesfaalem; Goerl, Kyle; Brown, Susan; et al.
Abstract: The SARS‐CoV‐2 virus is the causative agent of COVID‐19 and has undergone continuous mutations throughout the pandemic. The more transmissible Omicron variant has quickly spread and is replacing the Delta variant as the most prevalent strain globally, including in the United States. A new molecular assay that can detect and differentiate both the Delta and Omicron variants was developed. A collection of 660, 035 SARS‐CoV‐2 full‐ or near‐full genomes, including 169, 454 Delta variant and 24, 202 Omicron variant strains, were used for primer and probe designs. In silico data analysis predicted an assay coverage of >99% of all strains, including >99% of the Delta and >99% of Omicron strains. The Omicron variant differential test was designed based on the Δ31‐33 aa deletion in the N‐gene, which is present in the original B.1.1.529 main genotype, BA.1, as well as in BA.2 and BA.3 subtypes. Therefore, the assay should detect the majority of all Omicron variant strains. Standard curves generated with human clinical samples indicated that the PCR amplification efficiencies were 104%, 90.7% and 90.4% for the Omicron, Delta, and non‐Delta/non‐Omicron wild‐type genotypes, respectively. Correlation coefficients of the standard curves were all >0.99. The detection limit of the assay was 14.3, 32.0, and 21.5 copies per PCR reaction for Omicron, Delta, and wild‐type genotypes, respectively. The assay was designed to specifically detect SAR‐CoV‐2 strains. Selected samples with Omicron, Delta and wild‐type genotypes identified by the RT‐qPCR assay were also confirmed by sequencing. The assay did not detect any animal coronavirus‐positive samples that were tested. Human nasal swab samples that previously tested positive ( n = 182) or negative ( n = 42) for SARS‐CoV‐2 by the ThermoFisher TaqPath COVID‐19 Combo Kit, produced the same result with the new assay. Among positive samples, 55.5% (101/182), 23.1% (42/182), and 21.4% (39/182) were identified as Omicron, Delta, and non‐Omicron/non‐Delta wild‐type genotypes, respectively.